2003
DOI: 10.1016/s1534-5807(03)00022-4
|View full text |Cite
|
Sign up to set email alerts
|

A Time-Dependent Phase Shift in the Mammalian Unfolded Protein Response

Abstract: Unfolded or misfolded proteins in the endoplasmic reticulum (ER) must be refolded or degraded to maintain homeostasis of the ER. The ATF6 and IRE1-XBP1 pathways are important for the refolding process in mammalian cells; activation of these transcriptional programs culminates in induction of ER-localized molecular chaperones and folding enzymes. We show here that degradation of misfolded glycoprotein substrates requires transcriptional induction of EDEM (ER degradation-enhancing alpha-mannosidase-like protein)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

33
526
4
9

Year Published

2003
2003
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 626 publications
(572 citation statements)
references
References 32 publications
33
526
4
9
Order By: Relevance
“…9,15 The ER stress response is generally characterized by a time-dependent refolding response, which is followed by a refolding and degradation response. 16 The latter response is mediated by the XBP1 transcription factor, and we investigated whether cisplatin induces splicing of the mRNA for this transcription factor, an event carried out by the IRE1 Rnase. 17 We found that 40 lM cisplatin did not induce XBP1 splicing in 224 melanoma cells at any time-point tested, whereas treatment with thapsigargin, an inhibitor of the endoplasmic reticulum Ca 21 pump, did induce splicing (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…9,15 The ER stress response is generally characterized by a time-dependent refolding response, which is followed by a refolding and degradation response. 16 The latter response is mediated by the XBP1 transcription factor, and we investigated whether cisplatin induces splicing of the mRNA for this transcription factor, an event carried out by the IRE1 Rnase. 17 We found that 40 lM cisplatin did not induce XBP1 splicing in 224 melanoma cells at any time-point tested, whereas treatment with thapsigargin, an inhibitor of the endoplasmic reticulum Ca 21 pump, did induce splicing (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…During ER stress, ATF6 is activated rapidly by proteolysis, which generally occurs before the activation of XBP-1s. This observation suggests that ATF6-dependent gene transcription precedes XBP-1-dependent gene transcription and may provide insight into the cellular response during prolonged ER stress (48). However, because XBP-1 can also bind to the ERSE element (39), considerable redundancy exists in ERSE-dependent gene expression.…”
Section: The Upr Maintains Cellular Homeostasis During Er Stressmentioning
confidence: 99%
“…10 In a later phase, components of ER-associated degradation (ERAD), including ER degradation-enhancing a-mannosidase-like protein (EDEM), are transcriptionally induced to eliminate misfolded proteins in the ER by the ubiquitin-proteasome system. [11][12][13] The third involves activation of NFkB, a transcription factor known as a mediator of immune and antiapoptotic responses. 14 This pathway is designated ER overload response (EOR), because it is triggered by accumulation of membrane proteins in the ER.…”
mentioning
confidence: 99%